حكم موت الرَّحمة –الشفاعة- في الشريعة الإسلامية، رؤية تحليلية = The rule of euthanasia in Islamic law: analytical study - Niteh, Muhammad Yosef; Muhammad Husni, Ahmad (Fakulti Syariah & Undang-undang, Kolej Universiti Islam Selangor, 2019)
حرمت الشريعة الإسلامية الاعتداء على الأنفس بغير حق واعتبرت هذا الفعل من أعظم المفاسد على ظهر الأرض ومن أكبر الكبائر وأنكر المنكرات بعد الكفر بالله. فتكمن المشكلة في وجود بعض الأمراض المزمنة التي لا علاج لها ولا يُرجى شفاؤها كالأيدز وتليف الكبد والفشل الكُلوي ؛ لذلك دعا البعض بجواز قتله هؤلاء المرضى بدافع الشفقة أو الرحمة بهم حتى يتخلصوا من آلامهم المبرحة ؛ فحق الحياة مقدس في نظر الشريعة، فقد خلق الله الإنسان وألبسه ثوب الكرامة وفضًله على كثير ممن خلق بالعقل والعلم والبيان والنطق والصورة الحسنة والهيئة الشريفة وهونطفة في داخل الرحم وفي جميع أطواره إلى أن صار خلقاً آخر فتبارك الله الله أحسن الخالقين. لذلك فإن البحث يهدف إلى إبراز دراسة ت حكم موت الرحمة في الشريعة الإسلامية التي تقصد إلى حفظ النفس، والمقصود بموت الرحمة - أو كما يسميه البعض القتل بدافع الشفقة - هو : " تيسير موت الشخص الميئوس من شفائه، وهو في انتظار موته المحقق لا يتحمل الألم ، فيلح على الطبيب المعالج إنهاء حياته بطريقة خالية من الألم ".فنهجت الدراسة إلى المنهج الاستقرائي التحليلي من أجل إبراز آراء الفقهاء المعاصرين في حكم المسألة وكذلك آراء بعض الأطباء المسلمين ، ومعرفة حكم البلاء الذي يحل بالمسلم وكيفية الصبر على تحمل البلاء والرضا بقضاء الله وقدره وعدم القنوط من رحمة الله أو عدم اليأس من روح الله تعالى. وخلصت الدراسة أن فقهاء العصر الحديث بحرمة قتل الشفقة أو موت الرحمة ، وأن الإثم يقع على القاتل والمقتول معًا، ففي حالة اليأس من شفائ المريض الذي لا يُرجىَ شفاؤه يحرم على المريض أن يقتل نفسه، ويحرم على غيره قتله حتى لو أذن له في قتله. *********************************************************************************** The right to life is sacred in the eyes of the shariah. Allah created man and dignified him and preferred him on many creatures with the mind, knowledge, intonation, good shape and noble appearance when he was a sperm in the womb and in all his stages until he became another creature, bless be to Allah the best of creators. Thus, the Shariah prohibits attack on oneself unjustly and considered it an act of the greatest evils on earth and the greatest sins and evils after disbelief in Allah. The problem lies in the presence of some chronic diseases that cannot be treated and are not expected to be cured such as AIDS and cirrhosis of the liver and kidney failure; therefore some claim permissibility of killing patients of such diseases out of pity or compassion for them to get rid of their excruciating pain. Thus, the research aims to highlight the rule of euthanasia in Islamic law that aims at protection of life – euthanasia or mercy killing is “to facilitate the death of a person of a terminal ill; who is just waiting for his inevitable death and cannot bear the pain, and he asks the doctor to end his life in a manner free from pain.” The study adopted inductive and analytical approach to explain the views of the contemporary scholars on the issue as well as the views of some Muslim doctors, and to know the rule of trial which occurs to Muslim and how to be patient in enduring the hardship and to be satisfied with the decree of Allah and to avoid despair in the mercy of Allah.